Distal humeral fractures treated with ORIF or hemiarthroplasty: a matched-pair analyses - Weber, Marc Maximilian; Rausch, Valentin; Müller, Lars Peter; Hackl, Michael; Leschinger, Tim (Injury, 2025)
Introduction - Fractures of the distal humerus are common in older patients with osteoporotic bone, often presenting as complex, multi-fragmentary injuries involving the articular surface. This complexity complicates the decision between open reduction and internal fixation (ORIF) and total elbow arthroplasty (TEA), as both procedures carry specific risks. Hemiarthroplasty (HA) may be a viable alternative, yet few studies have compared its outcomes with those of ORIF. In this retrospective matched-pair study, we aimed to compare primary HA versus ORIF for complex distal humerus fractures. Our hypothesis was that HA could achieve functional outcomes equivalent to ORIF when joint reconstruction is not feasible. - Materials and methods - We matched 10 pairs of patients who underwent HA or ORIF between 2018 and 2022. Matching criteria included age, gender, and fracture classification (Orthopaedic Trauma Association (OTA) or Dubberley classification for coronal shear fractures). Functional outcomes were assessed using the Quick Disabilities of the Arm, Shoulder, and Hand (qDASH) score and the Mayo Elbow Performance Score (MEPS). The mean follow-up was 29 months for the HA group and 33 months for the ORIF group. - Results - Both treatment groups exhibited satisfactory functional outcomes. In the HA group, the median MEPS was 89.5 and a qDASH score of 21.6. Mean range of motion in extension/flexion was 105.9°. The ORIF group had a median MEPS of 81.5, a qDASH of 17 and a mean range of motion of 116.5°. No significant differences in functional outcomes were observed between the two groups - Conclusions - HA can yield functional results comparable to ORIF in managing complex distal humerus fractures. When ORIF is not feasible, HA is an effective alternative, particularly for physically active patients over 60 years, as it avoids the limitations associated with linked total elbow arthroplasty, such as weight restrictions and the risk of ulnar component loosening. - Level of evidence - Level III
Gesehen am 22.09.2025